Permainan Teka-Teki Silang dalam Pembelajaran Bahasa Indonesia - Jannah, Shakilla Feshtyani Miftahul; Salim, Herli (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The Corona Virus pandemic in 2019 is commonly known as Covid-19. Indonesia is one of the countries affected by Covid-19. As a result of the Covid-19 pandemic, researchers encountered obstacles when completing research because they could not go directly to the field. Games are one of the activities that are useful for integrating newly acquired words into word placements by students. Cross Puzzle is a game in which we need to fill in the empty space (in the form of a white box) with letters that form a word based on the directions given horizontally and downwards